134 HEMANGIOPERICYTOMA: A RARE INTRACRANIAL TUMOR. Issue 1 (1st January 2007) - Snead, C.; Hussain, S.; Burton, G. V.
Abstract : Introduction: Hemangiopericytoma (HPC) is a rare intracranial tumor comprising less than 1% of CNS tumors. HPC arises from pericytes surrounding the endothelial linings of blood vessels. The increased potential for local recurrence and metastases, compared with meningiomas, prompted the World Health Organization in 1993 to classify HPC in a separate category. HPC is closely related to anaplastic meningiomas, another high-grade dural-based malignant tumor. Anaplastic meningiomas metastasize less frequently but have shorter overall survival. We describe two patients with metastatic HPC. Case 1: A 32-year-old white female presented initially in 1986 with a left parietal meningioma treated with resection and radiation therapy. She had local recurrence in 1990 treated with resection and gamma knife surgery. In 2001, she developed a hepatic lesion and multiple asymptomatic lung lesions and underwent metastectomy for the hepatic lesion. She had local hepatic recurrence 1 year later treated with cryosurgery and radiation therapy. She required repeat cryosurgery in 2003 and 2005. She suffered a pathologic fracture of her left humerus in 2005 with histology consistent with metastatic HPC. She required another gamma knife surgery for a dural-based lesion near the foramen magnum in 2005. Her disease has remained stable over the past 12 months. Case 2: A 34-year-old white female presented in 1990 with a presumed meningioma. This lesion was resected, and postoperative radiation followed. She presented with subcostal pain in 2006. A CT scan demonstrated a 22 cm lesion in the right lobe of the liver. The resected tumor was consistent with HPC. She suffered local recurrence 3 months later with erosion into T1 vertebral body. She was treated with radiation therapy and intravenous bisphosphonates and has been progression free for 6 months. Discussion: HPCs are vascular malignant tumors arising from pericytes. HPCs tend to occur earlier in life (fourth decade), whereas meningiomas tend to occur in the sixth decade of life. HPCs are usually distinguishable from classic meningiomas based on light microscopy, but anaplastic meningiomas and HPC can have significant morphologic and immunohistochemical overlap. Special testing for epithelial membrane antigen, CD99, bcl-2, and FISH for specific chromoscome 14 abnormalities can help differentiate between anaplastic meningiomas and HPCs. Management of metastatic HPC typically involves surgery with or without radiation therapy.